The Urban Scale of Inclusion: Reflections and Proposals for Accessible Public Spaces - Sebastiano Marconcini (Igra Ustvarjalnosti, 2018)
The built environment plays a key role in fostrering human well-being and social participation and, in recent years, accessibility and inclusion have become central issues in the European policies for sustainable development. However, today’s design practice has revealed multiple criticalities in answering to the complexity of human needs that inclusive places should meet, especially at the urban scale. For this reason, it is necessary to rethink the processes of urban planning and design through the analysis of the limitations, and the possible solutions to overcome them, that the built environment presents. In particular, planners should play a new role in managing the tangible and intangible components that must characterize an inclusive design approach.